Survey of transcriptome analyses of hippocampal neurogenesis with focus on adult dentate gyrus stem cells - Micheli, Laura; Caruso, Maurizia; D’Andrea, Giorgio; Volpe, Daniel; Ceccarelli, Manuela; Tirone, Felice (Frontiers in Cell and Developmental Biology, 2025)
Adult mammalian brains generate new neurons throughout life in two main niches, the dentate gyrus of the hippocampus and the subventricular zone, starting from neural stem cells (NSCs). Adult hippocampal neurogenesis is crucial for learning and memory and decreases during aging. As defined in mouse models, NSCs, which are prevalently quiescent, develop into proliferating progenitor cells, neuroblasts, and immature and mature neurons. Two visions for NSC self-renewal in the dentate gyrus have been proposed, one postulating persistent self-renewal, with cycles of rest and reactivation even in old age, and the other proposing a short-lived NSC model. Single-cell RNA sequencing and clonal studies, discussed in this review, have shed light on the developmental steps of neurogenic cells and the modality of self-renewal, revealing the presence in the adult dentate gyrus of NSC heterogeneous populations, one long-lived and another rapidly depleted at an early age. Another relevant question is whether adult neurogenesis occurs in humans. A few single-cell RNA-seq studies show that new neurons, with prolonged neuronal maturation, are continuously generated at low frequency from stem/progenitor cells, which results in the accumulation of immature granule cell neurons. This suggests an important role of these cells in human neurogenesis and hence interspecies differences in the neurogenic process dynamics. This review is focused on transcriptomic studies that have faced these and other NSC issues by analyzing developmental trajectories of neural cells and NSCs gene expression profiles in specific experimental settings of hippocampal neurogenesis, and also in mouse models with deletion or overexpression of specific genes to reproduce neural pathologies.